FtsH4 protease controls biogenesis of the PSII complex by dual regulation of high light-inducible proteins - Krynická, Vendula; Skotnicová, Petra; Jackson, Philip J; Barnett, Samuel; Yu, Jianfeng; Wysocka, Anna; Kaňa, Radek; Dickman, Mark J; Nixon, Peter J; Hunter, C Neil; Komenda, Josef (Plant communications, 2023)
FtsH proteases are membrane-embedded proteolytic complexes important for protein quality control and regulation of various physiological processes in bacteria, mitochondria, and chloroplasts. Like most cyanobacteria, the model species Synechocystis sp. PCC 6803 contains four FtsH homologs, FtsH1-FtsH4. FtsH1-FtsH3 form two hetero-oligomeric complexes, FtsH1/3 and FtsH2/3, which play a pivotal role in acclimation to nutrient deficiency and photosystem II quality control, respectively. FtsH4 differs from the other three homologs by the formation of a homo-oligomeric complex, and together with Arabidopsis thaliana AtFtsH7/9 orthologs, it has been assigned to another phylogenetic group of unknown function. Our results exclude the possibility that Synechocystis FtsH4 structurally or functionally substitutes for the missing or non-functional FtsH2 subunit in the FtsH2/3 complex. Instead, we demonstrate that FtsH4 is involved in the biogenesis of photosystem II by dual regulation of high light-inducible proteins (Hlips). FtsH4 positively regulates expression of Hlips shortly after high light exposure but is also responsible for Hlip removal under conditions when their elevated levels are no longer needed. We provide experimental support for Hlips as proteolytic substrates of FtsH4. Fluorescent labeling of FtsH4 enabled us to assess its localization using advanced microscopic techniques. Results show that FtsH4 complexes are concentrated in well-defined membrane regions at the inner and outer periphery of the thylakoid system. Based on the identification of proteins that co-purified with the tagged FtsH4, we speculate that FtsH4 concentrates in special compartments in which the biogenesis of photosynthetic complexes takes place.
Keywords: tylakoidy; Photosystem II Protein Complex; photosystem II biogenesis; proteolysis; Thylakoids; Peptide Hydrolases; Chloroplasts; Arabidopsis; high light-inducible protein; FtsH4; proteasy; metaloproteasy; fylogeneze; Arabidopsis Proteins; fotosystém II (proteinový komplex); chloroplasty; Synechocystis; thylakoid; Phylogeny; Metalloproteases; proteiny huseníčku